Persentase Usaha E-Commerce Menurut Provinsi dan Model Penjualan Tahun 2018 - Suri Swedish; Butarbutar, Ruth Chaterina; Mutimmah Azzahra; Kireina Putri; Marpaung, Tasya Juliana; Syti Sarah Maesaroh (Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
The e-commerce ecosystem has rapidly evolved with various sales models, including sellers, resellers, and dropshippers. This study analyzes the percentage of e-commerce businesses based on sales models in 2018 using secondary data from industry reports. The findings indicate that the seller model dominated, followed by resellers, who played a significant role in product distribution. Meanwhile, the dropshipper model continued to grow due to its operational flexibility. These insights provide a better understanding of e- commerce trends and their implications for business strategies and industry policies moving forward.